REVIEW: Lies, media integrity and the new digital environment - Robie, David (Pacific Journalism Review, 2014)
Book reviews of: Stop Press: The Last Days of Newspapers, by Rachel Buchanan. Melbourne: Scribe, 2013. 169pp. ISBN 9781922070579; The New Front Page: New Media and The Rise of the Audience, by Tim Dunlop. Melbourne: Scribe, 2013. 258pp. ISBN 9781922070548Stop Press: The Last Days of Newspapers: When Rachel Buchanan penned a commissioned article entitled ‘From the classroom to the scrapheap’ for The Age last September, she railed against Australian journalism schools, in particular, against an alleged ‘lie’ and ‘little integrity’ of journalism education. ‘Between 2002 and 2012, enrolments in journalism degrees almost doubled,’ she noted about what was troubling her across the Tasman. ‘We now have the bizarre situation where there are more people studying journalism than there are working journalists.’ The New Front Page: New Media and the Rise of the Audience: The first in the series was The New Front Page: New Media and the Rise of the Audience, by political blogger pioneer Dr Tim Dunlop, who tackles the reasons why the mainstream media industry in Australia and New Zealand have been so slow to embrace digital media and innovative 'citizen journalism' apporaches.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjQxMzUvcGpyLnYyMGkxLjE5OA